O uso do nome social por alunos travestis e transexuais menores de idade nas escolas estaduais de Curitiba como forma de inclusão - Peres, Cilene Angelica Silva (2022)
This investigation refers to the approach on the use of the social name by transvestite and transsexual underage students in state schools in Curitiba, as a form of school inclusion. It was structured and based on the problem: Has the use of the social name by transvestite and transsexual underage students in state schools in Curitiba been showing effective results in school inclusion? The general objective is to analyze the contribution of the social name in the process of including transvestite and transsexual underage students in state schools in Curitiba. And, as specific objectives: to present the effectiveness of the norms to resolve the prejudice regarding gender identity; describe the daily life of underage students and the practices of using the social name in the school environment; and, to report the effectiveness of the use of the social name by transvestite and transsexual underage students from state schools in Curitiba. As a method, qualitative research, of exploratory character, with phenomenological method was used. The research was approved by the Research Ethics Committee through Technical Opinions No. 3,731,406 and 3,949,635, by Plataforma Brasil No. 24252719.4.0000.5688 /CAA, together with the data collection instruments, which are an interview guide, directed to teachers and parents of transvestite and transsexual students, the interview to students who use the social name and those who do not, and the Terms of Free and Informed Consent (ICF) of the interviewees; such as techniques, structured observation and document analysis.The results were positive regarding the effectiveness of the inclusion of transvestite and transsexual underage students through the use of the social name, demonstrating that although there is no effective knowledge of the rules, the adaptation to the use of the social name occurs naturally. It was concluded that the State College carries out actions addressing diversity as a way to settle prejudice and discrimination, sinning only, in the training of teachers. The school, as a decisive space in the construction of democratic relationships based on respect for sexual diversity, should continue promoting actions aimed at the entire school community and especially the family, because it is from their reception that the effectiveness of inclusion.